Photobiomodulation therapy does not attenuate fatigue and muscle damage in judo athletes: A randomized, triple-blind, placebo-controlled trial - Bet da Rosa Orssatto, L.; Detanico,D.; Kons, R.; Sakugawa, R. L.; Junior, J. N.; Diefenthaeler, F. (Frontiers in Physiology, 2019)
Fatigue and muscle damage negatively affect performance in lower limb exercises involving the stretch-shortening cycle in judo athletes during competition and training sessions. Photobiomodulation therapy has emerged as an effective non-invasive strategy to attenuate fatigue and muscle damage when applied before different types of exercises. Our objective was to investigate the effects of photobiomodulation therapy on fatigue and muscle damage in judo athletes. Sixteen judo athletes participated in the study (23.1 ± 3.8 years, 77.9 ± 14.9 kg, 173.1 ± 8.9 cm, 17.5 ± 7.3 body fat%, 12.9 ± 5.0 years of practice). Each participant received, in a randomized manner, photobiomodulation in one limb and placebo in the contralateral limb on the same day. Thereafter, subjects performed a stretch-shortening cycle protocol to induce muscle fatigue and damage. Countermovement jump (impulse, peak power, peak velocity, and peak force), echo intensity (rectus femoris and vastus lateralis), and muscle soreness were assessed at different time points before, during, immediately post, and 24 h and 48 h after the protocol. Muscle fatigue was detected due to reductions in countermovement jump impulse (14.7 ± 9.8 and 15.9 ± 15.5%), peak power (12.9 ± 8.5 and 11.9 ± 6.9%), velocity (8.6 ± 8.1 and 6.5 ± 6.0%), and force (7.0 ± 5.3 and 8.0 ± 6.1%) after the protocol (p < 0.001), for placebo and photobiomodulation therapy, respectively. Muscle damage was detected due to reductions in countermovement jump impulse (-6.1 ± 19.2% and-4.5 ± 9.2%, p<0.05), increases in echo intensity (rectus femoris, 21.0 ± 11.9 and 20.8 ± 9.0%; and vastus lateralis, 22.4 ± 23.2%; and 16.7 ± 23.8%; p < 0.001), and quadriceps muscle soreness (3.6 ± 1.6 and 3.5 ± 1.7 a.u; p < 0.011), 48 h after the protocol, for placebo and photobiomodulation therapy, respectively. No differences were observed between photobiomodulation therapy and placebo at any time points for any variables (p > 0.05), indicating no positive effect favoring photobiomodulation therapy. In conclusion, our findings suggest no effect of photobiomodulation therapy applied before exercise to reduce lower limb muscle fatigue and damage during and following a stretch-shortening cycle protocol in judo athletes.